WOMEN’S STRATEGIES FOR NEGOTIATING GENDER SOCIALIZATION BASED ON RELIGIOUS VALUES IN THE MODERN FAMILY - Jusnawati; Salwia; Abidah R. Delu (Referensi Islamika: Jurnal Studi Islam, 2026)
Gender socialization within the family is a crucial process that determines a woman’s future quality of life. The family serves as the primary agent for the structural transmission of gender norms to women. Studies on gender socialization in modern families generally highlight the dynamics of domestic role division and the negotiation of relationships. Nevertheless, women are still often positioned as passive recipients of the effects of social structures. This study aims to reconstruct this understanding by positioning women as active, reflective agents capable of interpreting, modifying, and negotiating gender norms based on religious values. This study employs a literature review approach through thematic synthesis of accredited national journal articles (minimum SINTA 4) and international theoretical literature. This study identified six strategies women employ in negotiating gender socialization: selective acceptance, reinterpretation of religious values, symbolic compromise and covert resistance, relational negotiation, management of dual roles, and cross-domain identity differentiation within the family and digital spaces. The analysis results indicate that gender socialization in modern families is a dialogical process between structure and agency. Research Implications – This study is limited to the specific literature cited for analysis, focusing on women’s strategies for negotiating gender socialization while considering religious values. Therefore, generalizations cannot be made to all modern families, which have distinct specific conditions. The findings of this study are expected to contribute to the development of gender studies in Indonesia at the micro level. This study not only examines women’s strategies for addressing gender value contradictions but also views women as active individuals living within both modern families and digital spaces, who reinterpret religious teachings to apply them in the process of gender socialization at the family level.